OPTIMASI SECONDARY SKIN UNTUK KUALITAS PENCAHAYAAN ALAMI. STUDI KASUS GEDUNG FAKULTAS SENI DAN DESAIN UNIVERITAS NEGERI SURABAYA - Fahrezi, Muhammad Farel; Widiastuti, Ratih (MODUL, 2023)
Façade as the outer layer of building has an important role in distributing the sunlight into the building. Building with maximum natural lighting will support energy saving campaigns. This study discussed the evaluation of building façade to support natural lighting distribution inside the rooms. The study applied simulation method using DIALux Evo software. The results from simulations compared to the lighting standard from SNI 6197-2011. The study object was the Faculty Building of Art and Design of State University of Surabaya. According to the simulation, 40% - 70% distribution of average natural lighting intensity exceeded 1000 Lux. It caused people who stayed inside the room to feel uncomfortable due to glare. To reduce the light intensity inside the room, additional layers on the exterior façade were added. The results from simulation confirmed the secondary layer on the exterior facade was able to reduce the natural lighting intensity from 279 Lux to 1112 Lux in the morning and from 256 Lux to 879 Lux in the afternoon. Thus, it can minimize the effect of glare inside the room.